THE EFFECT OF WORK EXPERIENCE AND CREDIT-DISBURSEMENT TARGET ACHIEVEMENT ON THE PERFORMANCE QUALITY OF BRI MANTRI AT THE METRO BRANCH - Intan Anggitia Prebrianti; Agus Wahyudi (International Journal of Multidisciplinary Reseach, 2026)
This study examines the effects of work experience and credit-disbursement target achievement on the performance quality of BRI Mantri at the Metro Branch. The study used a quantitative causal-associative survey design. The population comprised 93 Mantri, with 75 respondents selected using the Slovin formula at a 5% margin of error. Data were collected using a five-point Likert-scale questionnaire and analyzed in SPSS through descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, an F-test, and the coefficient of determination. The instruments were valid and reliable, with Cronbach's alpha values of 0.948, 0.946, and 0.898. Work experience had a positive and significant effect on performance quality (B = 0.480; t = 3.849; p < 0.001), while target achievement also had a positive and significant effect (B = 0.336; t = 2.885; p = 0.005). Simultaneously, both variables significantly affected performance quality (F = 189.929; p < 0.001) and explained 84.1% of its variance. Work experience was the more dominant predictor, highlighting the importance of structured mentoring, field exposure, and balanced target management.